On the photoluminescence in triarylmethyl-centered mono-, di-, and multiradicals - Daniel Straub; Markus Gross; Mona E. Arnold; Julia Zolg; Alexander J. C. Kuehne (Beilstein Journal of Organic Chemistry)
Organic radicals with light-emitting properties and exceptional stability offer exciting opportunities to address spin-statistical limitations in organic electronics and advance quantum technologies. These radicals, acting as small molecular magnets, exhibit sensitivity to minute magnetic fields and can be tailored with diverse spin centers, making them ideal for spin-optical interfaces, representing key components in quantum communication systems. Furthermore, their ability to form organized, higher-dimensional assemblies presents a promising avenue for overcoming scalability challenges in quantum technologies. Despite their potential, achieving high luminescence quantum yields has largely been limited to donor-functionalized monoradicals, and a detailed understanding of the luminescent behavior of open-shell organic molecules remains elusive. This review delves into the photoluminescent properties and spin ground states of trityl-based mono-, di-, and multiradicals, examining the strategies employed to enhance their performance. Additionally, we review predictive methods for determining the luminescence and spin states of radicals, highlighting critical unresolved questions that must be addressed to unlock the full potential of trityl-based radicals in advanced technological applications.